2007
DOI: 10.1159/000101409
|View full text |Cite
|
Sign up to set email alerts
|

IL-2-Induced IL-9 Production by Allergen-Specific Human Helper T Cell Clones

Abstract: Background: IL-9 is an important cytokine in allergic diseases such as asthma, atopic dermatitis, etc. T helper (Th) cells seem to be the main source of IL-9. Cellular and molecular mechanisms of IL-9 production by human Th cells have been poorly understood. Methods:Dermatophagoides farinae(Der f)-specific Th clones were established from peripheral blood lymphocytes of atopic asthmatics, and cytokine synthesis in response to various stimuli was determined by specific ELISAs. Results: IL-9 was produced by 14 of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Consistent with our observation, Fung et al and Kajiyama et al showed that IL-2 induced IL-9 production in HTLV-1-infected cell lines and allergen-specific human helper T-cell clones. 35,36 Further analysis of the IL-9 promoter would be helpful to identify transcriptional elements and epigenetic events that are responsible for IL-2-induced IL-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our observation, Fung et al and Kajiyama et al showed that IL-2 induced IL-9 production in HTLV-1-infected cell lines and allergen-specific human helper T-cell clones. 35,36 Further analysis of the IL-9 promoter would be helpful to identify transcriptional elements and epigenetic events that are responsible for IL-2-induced IL-9 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Gene patterns associated with the development of a Th2 cellular immune response were evident in allergic patients' samples, but absent in those from tolerant individuals (Figure 4). Networks deriving from allergic patients' samples also contained the cytokine IL-9, a signaling molecule secreted from memory T cells (Kajiyama et al, 2007) that promotes IgE production by B cells and has been implicated in allergic diseases such as asthma and food allergy (Ying et al, 2002;Forbes et al, 2008). Recently, IL-9producing T cells were found to be a distinct T-cell population, provisionally termed Th9 cells, deriving from Th2 cells following programming in the presence of TGF-b (Veldhoen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…IRF4 is known to be essential for IL-9 production, and now we found that NFATc1 also has an effect on IL-9 production either through a direct effect on the promoter of IL-9 (alone or along with IRF4) or through its influence on IL-2 E14 or IL-4, which are required for IL-9 production. In fact, TGF-β and IL-4 are required to induce T H 9 differentiation.…”
Section: Resultsmentioning
confidence: 50%